miR-513c-5p Suppression Aggravates Pyroptosis of Endothelial Cell in Deep Venous Thrombosis by Promoting Caspase-1 - Chu, Chu; Wang, Bin; Zhang, Zhen; Liu, Wen; Sun, Shangwen; Liang, Gang; Zhang, Xiaoshan; An, Hongqiang; Wei, Ran; Zhu, Xiaoxiao; Guo, Qiang; Zhao, Lin; et al. (Frontiers in Cell and Developmental Biology, 2022)
Deep vein thrombosis (DVT) is a common peripheral vascular disease. Secondary pulmonary embolism (PE) caused by DVT leads to substantial patient death. Inflammation has been suggested as a key factor in the pathophysiology of DVT, however, involvement of pyroptosis related inflammatory factors in DVT formation remain unclear. Here, we proposed that post-transcriptional modification of Caspase-1 might be a crucial trigger for enhanced pyroptosis in vascular endothelial cells (VECs), and consequently contributed to severer symptoms in DVT patients. In order to explore the involvement of pyroptosis in DVT, peripheral blood mononuclear cells were collected from 30 DVT patients, and comparing with the healthy controls, we found Caspase-1 were increased both in mRNA and protein levels. miRNA microarray analysis demonstrated that down-regulated miR-513c-5p was significantly negatively correlated with the expression of Caspase-1. In vitro assays suggested that miR-513c-5p overexpression could ameliorate the expression of Caspase-1, and thus decreased the production of cleaved gasdermin D (GSDMD) as well as interleukin (IL)-1β and IL-18 in VECs. Dual luciferase reporter assay identified direct binding between miR-513c-5p and the 3' untranslated region of Caspase-1 encoding gene. Administration of miR-513c-5p mimics through tail vein injection or Caspase-1 inhibitor (vx-765) by intraperitoneal injection remarkably decreased the volume of blood clots in vivo, whereas miR-513c-5p inhibitor aggravated thrombosis formation and this effect was dramatically weakened when treated in combination with vx-765. Collectively, these results revealed that pyroptosis of VECs induced by decreased miR-513c-5p was involved in DVT progression and indicated a potential therapeutic strategy of targeting the miR-513c-5p/Caspase-1/GSDMD signal axis for DVT management.